Advances in the Profiling of Single‐Cell DNA Modifications. Issue 10 (14th May 2019) - Bai, Dongsheng; Yi, Chengqi
Abstract: Epigenetic modifications on DNA include canonical 5‐methylcytosine (5mC) and its iteratively oxidized derivatives mediated by TET dioxygenase: 5‐hydroxymethylcytosine (5hmC), 5‐formylcytosine (5fC), and 5‐carboxycytosine (5caC). All of them have been recognized to play important roles in gene expression regulation and to be indispensable for normal mammalian reproduction and development. In order to understand the mechanisms underlying these roles, over the past few decades, technical advances have been made to comprehensively profile the distribution pattern of bulk epigenetic modifications in genomic DNA. Recently, single‐cell methods have identified the epigenetic patterns even within an individual cell. This review focuses on single‐cell DNA epigenetic modifications sequencing technologies and their applications, and gives prospects on the development of single‐cell methods based on bisulfite‐free strategy. Abstract : DNA modifications play important roles in gene expression regulation. These epigenomic marks are cell type‐specific and developmentally regulated. Emerging single‐cell profiling methods are being developed with the exciting potential to transform our knowledge of gene regulation and extend to provide unique insights into the dynamic of DNA methylation and demethylation and the extent of cell heterogeneity.